In vitro Evaluation of BACT/ALERT® VIRTUO®, BACT/ALERT 3D®, and BACTEC™ FX Automated Blood Culture Systems for Detection of Microbial Pathogens Using Simulated Human Blood Samples - Menchinelli, Giulia; Liotti, Flora Marzia; Fiori, Barbara; De Angelis, Giulia; D'Inzeo, Tiziana; Giordano, Liliana; Posteraro, Brunella; Sabbatucci, Michela; Sanguinetti, Maurizio; Spanu, Teresa (Frontiers in Microbiology, 2019)
Blood culture (BC) is still the standard for diagnosing bloodstream infections (BSIs), especially those caused by bacteria and fungi. Infection-complicating sepsis or septic shock often occurs at BSI onset, making necessary to improve the diagnostic yield of positive BCs. Among the BC systems currently available, the BACT/ALERT® VIRTUO® (VIRTUO) system has been developed to shorten time to detection (TTD) of positive BCs. In this study, we assessed TTD for 330 clinically relevant species including 14 Gram-positive, 14 Gram-negative, and 5 yeast isolates in spiked human blood samples that were tested in parallel with VIRTUO BACT/ALERT 3D (BTA3D) and BACTEC™ FX (BACTEC) systems. We inoculated 30 colony-forming unit (CFU) from each microbial suspension into BACT/ALERT® Plus or BACTEC™ FX Plus (aerobic/anaerobic or pediatric) BC bottles, and we used two different blood volumes to simulate, respectively, the BCs collected from adult and pediatric patients. Of 2,610 bottles tested, 2,600 (99.6%) signaled positive in the three systems. Only the BACTEC system did not detect Staphylococcus lugdunensis isolates in anaerobic bottles. Among adult simulated cultures, the median TTD was significantly shorter for aerobic/anaerobic bottles incubated in VIRTUO (11.6 h and 10.1 h) compared to bottles incubated in either BTA3D (13.3 h and 12.3 h) or BACTEC (13.5 h and 12.2 h) system. Among pediatric simulated cultures, the median TTD was significantly shorter for bottles incubated in VIRTUO (11.2 h) compared to bottles incubated in either the BTA3D (13.0 h) or BACTEC (12.5 h) system. Compared to BTA3D and/or BACTEC systems, VIRTUO allowed faster growth detection for most of the 33 microbial species tested. Notable examples were Salmonella spp. (7.4 h by VIRTUO versus 10.1 h and 9.2 h by either BTA3D or BACTEC) and Streptococcus agalactiae (8.1 h by VIRTUO versus 10.3 h and 9.4 h by either BTA3D or BACTEC). The few notable exceptions included Stenotrophomonas maltophilia and some Candida species. Together, these findings confirm that VIRTUO has greater potential of improving the laboratory detection of bacteremia and fungemia than the progenitor BTA3D or the competitor BACTEC system.